Evaluating the Dimensionality and Psychometric Properties of the Brief Self-Control Scale Amongst Chinese University Students - Fung, Sai-fu; Kong, Chris Yiu Wah; Huang, Qian (Frontiers in Psychology, 2020)
This study evaluated the dimensionality and psychometric properties of the Brief Self-Control Scale (BSCS) using a sample of university students in mainland China. Nine hundred and three students from a Chinese university participated in this study. The internal consistency, criterion validity, factorial validity and construct validity of the scale were examined. The Chinese versions of the BSCS demonstrated good internal consistency. The BSCS also showed significant moderate correlations with other construct-related scales. Exploratory factor analysis and confirmatory factor analysis suggested that only a modified 11-item BSCS with a four-factor structure was a good model fit in the sample of Chinese university students. The implications for research and theoretical development are discussed.